PENGARUH MORALITAS INDIVIDU, ASIMETRI INFORMASI, DAN EFEKTIVITAS PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PADA LPD DI KECAMATAN TEGALLALANG - Ni Komang Nitimiani; Anak Agung Ketut Agus Suardika (UNHI Press, 2020)
This study aims to determine the effect of individual morality, information asymmetry, and the effectiveness of internal control on the tendency of accounting fraud on LPD in Tegallalang sub- district. The population in this study were all LPD employees in Tegallalang District. The number of samples taken was 168 employees, with a purposive sampling method. This research method uses quantitative research methods with primary data obtained from questionnaire data measured using a Likert scale. The analysis technique used is multiple regression analysis using SPSS 21.00 for Windows. The results of this study indicate that Individual Morality and Effectiveness of Internal Control have a negative and significant effect on the tendency of accounting fraud in the LPD in Tegallalang District, while the Asymmetry of Information has a positive and significant effect on the tendency for accounting fraud in the LPD in Tegallalang District.